2008
DOI: 10.1128/jb.00178-08
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Organization of the Region Encoding the Synthesis of the Flagellar Filament in Pseudomonas fluorescens

Abstract: Pseudomonas fluorescens F113 is motile by means of type b flagella. Analysis of the region encoding the synthesis of the flagellar filament has shown a transcriptional organization different from that of type a flagella. Additionally to the promoters driving fliC, fliD, and fleQ expression, we have found promoters upstream of the flaG gene and the fliST operon. These promoters were functional in vivo. Both promoters have been mapped and appear to be dependent on the vegetative sigma factor and independent of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
(26 reference statements)
1
13
0
2
Order By: Relevance
“…2 and 3). The results presented here corroborate that flagellar biosynthesis is differently regulated in diverse Pseudomonas strains (71).…”
Section: Resultssupporting
confidence: 78%
“…2 and 3). The results presented here corroborate that flagellar biosynthesis is differently regulated in diverse Pseudomonas strains (71).…”
Section: Resultssupporting
confidence: 78%
“…2A). By this approach, we would be able to detect amplification only where the mRNA is polycistronic for the adjacent genes probed (35). We observed that no amplification occurred only between 3= fliF L and 5= lafA2, and between 3= lafA2 and 5= lafA1 (see Fig.…”
Section: Resultsmentioning
confidence: 78%
“…S4): two of the reactions amplified fragments of the coding sequence of each contiguous gene (positive control), while the third amplified a fragment encompassing the intergenic region between the target genes (35).…”
Section: Methodsmentioning
confidence: 99%
“…Several of these genes in F113 have been previously analyzed [44,45] and regulation of flagella synthesis requires the master regulatory gene fleQ [46]. Besides these genes, F113 chromosome harbors another 41 kb flagella locus containing 40 CDSs (PSF113_0738-PSF113_0782), which is not present in any other Pseudomonas genome, with the exception of P. extremaustralis (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%